Fetal biometry and amniotic fluid index from the 14th to the 41st week at 3400 meters altitude and comparing these parameters with those obtained at other altitude levels - Villamonte, Wilfredo (2013)
Objectives: To know normal biometry tables and amniotic fluid index at 3400 m above sea level by ultrasound and comparation with others tables from different levels of altitude. Design: Prospective and descriptive study performed by one ultrasonographer from January of 2007 to December of 2010. 1188 normal women with singleton pregnancies National Hospital Adolfo Guevara Velazco of EsSalud in Cusco. Results: We obtained tables with 5th and 95th centiles and median of fetal biometrical parameters from 14 to 41 weeks of gestational age of biparietal diameter, frontoccipital diameter, cephalic circumference, abdominal circumference, femur length and amniotic fluid index. Conclusions: The fetal biometry increases throughout the pregnancy at 3400 m above sea level. It shows lower at the end of pregnancy in relation to London, while following the same trend in relation to Lima but in reverse and increased throughout gestation in relationship to Cerro de Pasco.